Effects of occlusal splints on shoulder strength and activation. (29th March 2019) - Dias, Amândio; Redinha, Luís; Vaz, João R.; Cordeiro, Nuno; Silva, Luís; Pezarat–Correia, Pedro
Abstract: Introduction: The use of oral appliances to enhance sports performance has been advocated by some authors, however, studies addressing the effectiveness of these strategies are inconclusive. Methods: Here we investigate the effects of dental occlusions on shoulder strength. Fourteen healthy male subjects (age = 21.67 ± 0.86 years) without temporomandibular joint (TMJ) disorder participated in this study. Isokinetic strength was evaluated in shoulder abduction/adduction and arm external/internal rotation tests. Three randomised conditions were assessed: (1) occlusal splint (OS), which repositioned the TMJ in centric relation; (2) placebo splint (PS); and (3) no-splint (N). The strength tests were performed at a speed of 60°/sec in concentric mode. Muscle activity was measured by surface electromyography (EMG) in the main muscles engaged in the movements. Results: Significant differences in peak torque between OS and both of the other experimental conditions were found in some of the analyzed variables. Moreover, there was significantly higher muscular EMG activation in the OS condition when compared to the other conditions for some of the tested muscles. These data suggest that splints may have a positive ergogenic effect on shoulder muscular strength in healthy male subjects. Conclusion: OS may provide an advantage for healthy subjects engaged in sports whereby shoulder and arm strength are important for performance. Key messages: Occlusal splints in centric relation position have an ergogenic effect, by increasing strength and muscle activation on shoulder in healthy subjects. These results could have implications for sports or other physical activities were arm and shoulder strength are important.